Qualitative and quantitative water investigation of Erin-Ijesha (Olumirin) Waterfall, Erin-Ijesha, Nigeria - Joseph O. Adejuwon; Faith I. George (Heliyon, 2024)
This study focused on the assessment of water quality in Erin-Ijesha (Olumirin) Waterfall, a prominent natural attraction in southwestern Nigeria. The physiochemical parameters, heavy metal concentrations, and bacteriological characteristics were examined in the upstream, midstream, and downstream sections, to ensure the resource quality and safety from harm. The results revealed notable variations in water quality. The pH, Total Dissolved Solids, Electrical Conductivity, and Temperature were highest in the midstream while Total Hardness, Alkalinity, salinity, Chloride, sulphate, Phosphate, Nitrate, Calcium, and Magnesium were highest in the downstream section. The physicochemical parameters were within the acceptable limits of World Health Organization (WHO), United States Environmental Protection Agency (USEPA), and the Standard Organization of Nigeria (SON) standards, except the pH, temperature, and Total Hardness were higher than the acceptable limits of 6.5–8.5, <25 °C or >50 °C and 50 mg/L in all the sections. Iron was above the WHO, USEPA, and SON permissible limits of 3.0 mg/L in all the sections of the river while there was no indication of copper, lead, and cadmium. Bacterial contamination, particularly the presence of E. coli, exceeded recommended safety thresholds. The Total Bacterial Count (TBC) exceeded safety limits by 0.1 million cfu/mL in the downstream. The mean of the parameters was higher in some instances, and sometimes lower than the values in the various sections of the river. A significant relationship existed between most physical, chemical, and bacteriological parameters at p < 0.01. The appraisal of water quality in Olumirin Waterfalls emphasizes the need for proactive measures to ensure water safety, preserve ecosystems, and promote responsible water resource management.